Safety and efficacy of trifluridine/tipiracil in previously treated metastatic colorectal cancer: PRECONNECT Turkey - DANE, FAYSAL (My University, 2022)
Background: The efficacy and safety of trifluridine/tipiracil (FTD/TPI) for third-line treatment of metastatic colorectal cancer have been demonstrated. The authors present the Turkish post hoc analysis of the PRECONNECT study. Methods: An international, multicenter, single-arm, open-label, phase IIIb trial evaluating FTD/TPI in patients with >= 2 previous lines of chemotherapy for metastatic colorectal cancer was conducted. The primary end point was safety. Results: In this Turkish cohort (n = 100; eight centers), the most frequent treatment-emergent adverse event was neutropenia (48%). Median progression-free survival was 3.0 months; disease control rate was 36%; quality of life remained stable. Conclusion: Outcomes with FTD/TPI in Turkey are consistent with previous studies and confirm the efficacy and safety of FTD/TPI treatment in the third-line setting.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Health Sciences; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED)